A Clinical and Quantitative Bacteriological Study on Wound Infection and Effects of Some Topical Anti-Microbial Agents on Wound Healing - Sandipan Gupta; Subir K. Dutta; A. C. Ganguli (Indian Journal of Plastic Surgery)
A total of 165 cases of burns were evaluated by surface swab culture and quantitative biopsy cultures. Staphylococci was the most frequent single organism isolated, although Gram-negatives exceeded the Gram-positives ones. Surface swab culture was found to be a generally reliable indication in 70% of the cases. Framycetin was found to be superior to Povidone iodine and Silver sulphadiazine as far as topical antimicrobial agents are concerned.